Emerging Roles of lncRNAs in the Formation and Progression of Colorectal Cancer - He, Qinglian; Long, Jiali; Yin, Yuting; Li, Yuling; Lei, Xue; Li, Ziqi; Zhu, Wei (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is the primary cause of cancer-related death worldwide; however, specific and sensitive tools for the early diagnosis and targeted therapy of CRC are currently lacking. High-throughput sequencing technology revealed that gene expression of long-chain non-coding RNAs (lncRNAs) in a number of cancers directly or indirectly interferes with various biological processes. Emerging evidence suggests that lncRNAs regulate target genes and play an important role in the biological processes of malignancies, including CRC. Many carcinostatic/oncogenic lncRNAs have been identified as biomarkers for metastasis and prognosis in CRC; hence, they serve as therapeutic tools. In this article, we systematically review the literature on the disordered lncRNAs in CRC from four aspects: DNA transcription, RNA level regulation, post-translational level, and the translation of lncRNAs into polypeptides. Subsequently, we analyze the mechanism through which lncRNAs participate in the biological process of CRC. Finally, we discuss the application and prospects of these lncRNAs in CRC.